Penerapan Model Snowball Throwing dapat Meningkatkan Keterampilan Menyimak Cerita Anak pada Siswa Kelas VI UPTD SDN Sejati 6 Kecamatan Camplong Kabupaten Sampang Tahun Pelajaran 2019/2020 - Mohammad Fadil (Journal on Education, 2023)
The Snowball Throwing learning model is suitable for use in Indonesian lessons, especially listening skills, because the child will concentrate when the teacher reads the story. If his attention is distracted he will not be able to ask questions and answer questions given by his friends. The purpose of this study is to describe the use of the Snowball Throwing learning model to improve student learning outcomes in listening to children's stories and also to describe the use of the Snowball Throwing model to increase student activity in listening to children's stories. This study uses PTK. The implementation of CAR refers to the CAR cycle model by Kemmis and Taggart which includes four stages, namely 1) planning, 2) implementing actions, 3) observing, and 4) reflecting. The application of the Snowball Throwing model is proven to improve students' listening skills. This can be proven by the increasing scores obtained by students in cycle 1 and cycle 2. So in each cycle and each meeting, the scores obtained by students are increasing. It can be concluded that in this study it is proven that the application of the Snowball Throwing model can improve listening skills in learning Indonesian for class VI students of UPTD SDN Sejati 6, Camplong Sampang District.